The Performative University: 'Targets', 'Terror' and 'Taking Back Freedom' in Academia. Issue 4 (September 2020) - Jones, David R; Visser, Max; Stokes, Peter; Örtenblad, Anders; Deem, Rosemary; Rodgers, Peter; Tarba, Shlomo Y
This special issue assembles eight papers which provide insights into the working lives of early career to more senior academics, from several different countries. The first common theme which emerges is around the predominance of 'targets', enacting aspects of quantification and the ideal of perfect control and fabrication. The second theme is about the ensuing precarious evocation of 'terror' impacting on mental well-being, albeit enacted in diverse ways. Furthermore, several papers highlight a particular type of response, beyond complicity to 'take freedom back' (the third theme). This freedom is used to assert an emerging parallel form of resistance over time, from overt, planned, institutional collective representation towards more informal, post-recognition forms of collaborative, covert, counter spaces (both virtually and physically). Such resistance is underpinned by a collective care, generosity and embrace of vulnerability, whereby a reflexive collegiality is enacted. We feel that these emergent practices should encourage senior management, including vice-chancellors, to rethink performative practices. Situating the papers in the context of the current coronavirus crisis, they point towards new forms of seeing and organising which open up, rather than close down, academic freedom to unleash collaborative emancipatory power so as to contribute to the public and ecological good.